2021
DOI: 10.1080/14397595.2020.1868667
|View full text |Cite
|
Sign up to set email alerts
|

Association of health-related quality of life with self-management and satisfaction of relationship with healthcare professionals in female patients with rheumatoid arthritis

Abstract: Objectives We explored associations between health-related quality of life (QOL) with self-management and satisfaction with relationships with medical professionals among female rheumatoid arthritis (RA) patients. Methods Female RA outpatients completed anonymized self-reported questionnaires. Their confidence in self-managing different aspects of RA and satisfaction with relationships with medical professionals were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…QOL of RA patients was evaluated by EQ5D score [ 33 ]. In agreement with previous evidence [ 7 , 13 , 34 , 35 ], the EQ5D score in our cohort also affected all aspects of satisfaction (treatment cost, efficacy, ADL, and global treatment), indicating that the improvement of EQ5D should be critical for better RA treatment and patient satisfaction. Because EQ5D showed interacted with disease duration, VAS pain, and VAS general in terms of treatment cost, treatment effect, ADL, and global treatment, the satisfaction associated with EQ5D can be separately assessed by each factor.…”
Section: Discussionsupporting
confidence: 92%
“…QOL of RA patients was evaluated by EQ5D score [ 33 ]. In agreement with previous evidence [ 7 , 13 , 34 , 35 ], the EQ5D score in our cohort also affected all aspects of satisfaction (treatment cost, efficacy, ADL, and global treatment), indicating that the improvement of EQ5D should be critical for better RA treatment and patient satisfaction. Because EQ5D showed interacted with disease duration, VAS pain, and VAS general in terms of treatment cost, treatment effect, ADL, and global treatment, the satisfaction associated with EQ5D can be separately assessed by each factor.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies use the score of the QoL as an indicator of the assessment of pharmacological and non-pharmacological interventions in the management of RA. [ 3 6 ] The relationships between RA severity, as measured by Disease Activity Score-28 (DAS-28) for Rheumatoid Arthritis with C-reactive protein (CRP) or erythrocyte sedimentation rate (ESR), and QoL have been thoroughly investigated, and it has been discovered that a higher DAS-28 is associated with QoL impairment. [ 7 , 8 ] Several studies have assessed the hematological indices and ratios in RA patients and found a nonsignificant relationship between mean platelet volume (MPV) and disease severity in treated RA patients,[ 9 ] no association between red cell distribution width (RDW) with complications of RA,[ 10 ] association between platelet-to-lymphocyte ratio (PLR) and the chronicity of the disease,[ 11 ] and significantly higher neutrophil-to-lymphocyte ratio (NLR) in patients with active RA than those in remission.…”
Section: Introductionmentioning
confidence: 99%